Catalytic properties of Au electrodes modified by an underlayer of Pd - Juárez, María Fernanda; Soldano, Germán; Guesmi, Hazar; Tielens, Frederik; Santos, Elizabeth (Surface science, 2015)
Bimetallic catalysts have manifold technological applications; their reactivity can greatly exceed that of the original single metals. In this work, we investigate an ideal model-system consisting of a complete monolayer of Pd underneath the surface of Au(111). First, we investigate the stability of this system, and then its interaction with hydrogen. We analyze in detail the energetics and the electronic interactions for the Volmer step of the hydrogen evolution reaction (HER), and the further absorption below the surface layer of gold. We combine Density Functional Theory based on computational techniques with the theory of electrocatalysis. [Display omitted] •Electronic interactions of hydrogen with Pd–Au alloys have been investigated.•The space and energy distribution of the electronic states has been analyzed.•Adsorption/absorption processes have been explored in an electrochemical environment.•Promising for hydrogen storage (exothermic absorption/high de-absorption barrier)